Development of a Toolkit to Measure and Value Community Severance Due to Traffic. (June 2017) - Mindell, Jennifer S; Jones, Peter; Haklay, Muki; Vaughan, Laura; Scholes, Shaun; Groce, Nora; Anciaes, Paulo; Stockton, Jemima; Dhanani, Ashley
Abstract : Background: Heavily motorised large roads can interfere with individuals' ability to access the goods, services, and people they need for a healthy life ('community severance'). It also reduces the amenity value of streets as active social spaces. Interference with active living affects particularly children, denied freedom to explore and play, and older people, whose slower walking speeds limit their ability to cross roads. Despite this, there is a lack of tools to identify, measure, and study community severance caused by busy roads. This project aimed to develop a suite of tools to measure community severance, and validate the tools through triangulation of findings from different data sources. Methods: New tools include: participatory mapping - engaging local residents and community members to provide qualitative data on the locality and their relationship with it; a health and neighbourhood mobility survey to collect data from a random sample of local residents on their perceptions of walking around their area and on their health and mental wellbeing; a community severance valuation tool, based on data from stated preference; walkability models; and video surveys, to determine pedestrian and motorised traffic flows and pedestrian crossing behaviours. In addition, spatial analysis, using space syntax, and street audits, to assess the pedestrian environment quality, were used. These were all tested in Finchley Road, a busy arterial road in North London and refined in case studies in Southend-on-Sea and Birmingham, UK. Results: Despite having a high walking potential, Finchley Road is unpleasant for pedestrians due to high traffic levels, the associated air and noise pollution, and the lack or poor quality of pedestrian crossing facilities. This has a negative impact on mobility and accessibility for local residents and on the quality of their walking trips. In the Finchley Road case study, people living ≤100m from their busiest road were more likely to be in the lowest decile for wellbeing than people living further away (p=0.007). The analyses showed coherence between the findings from the different measurement tools applied individually and revealed interconnections between factors which contribute to severance. Conclusions: Coherence of qualitative & quantitative findings supports the validity of the tools. The toolkit will be available online in 2017 from www.ucl.ac.uk/street-mobility/toolkit for use by local communities, practitioners, and researchers. By providing valuations of the impacts of community severance on the local community, policy-makers and practitioners can prepare business cases for expenditure to reduce severance.